2011
DOI: 10.1016/j.tet.2011.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Function oriented synthesis: preparation and initial biological evaluation of new A-ring-modified bryologs

Abstract: The synthesis and biological evaluation of the first members of a new series of designed bryostatin A-ring analogues (bryologs) are described. An advanced intermediate is produced that allows for step economical access to diverse analogs. The first of these analogues, bearing side chains of completely different polarities from alkyl to hydroxyl and carboxyl functionalities, were evaluated. All exhibit potent protein kinase C binding (54.7 to 2.4 nM) with affinities increasing with decreasing side chain polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…A number of simplified bryostatin analogues (often called "bryologs") have been synthesized using methods such as functionoriented synthesis. This technique was employed by Wender and other workers to develop simplified analogues with comparable or much improved activities, in some cases orders of magnitude in in vitro assays [136][137][138]. Further information was given in a review by Newman [139] and in a recent 2013 paper by the Keck group [140].…”
Section: Bryostatin 1 and "Latent" Hivmentioning
confidence: 99%
“…A number of simplified bryostatin analogues (often called "bryologs") have been synthesized using methods such as functionoriented synthesis. This technique was employed by Wender and other workers to develop simplified analogues with comparable or much improved activities, in some cases orders of magnitude in in vitro assays [136][137][138]. Further information was given in a review by Newman [139] and in a recent 2013 paper by the Keck group [140].…”
Section: Bryostatin 1 and "Latent" Hivmentioning
confidence: 99%
“…[6d] These studies were primarily driven by the guiding principle that the bryostatin core structure could be divided into the upper "binding" or "recognition domain" (C1-C14) and lower "spacer domain" (C15-C27) according to its interactions with PKC ( Figure 9). [86] Studies on bryologs have examined the significance of the Aring, [87] the Bring, [88] the C20 [89] and C7 side chains, [90] as well as de novo structures, [91] among others. [92] Notable examples of analogues include picolog synthesized by Wender et al (reported in 2002 with aP KC binding affinity of 0.25 nmol L À1 ), which was synthesized in 29 steps with al ongest linear sequence of 19 steps.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Synthetic approaches to generating the bottom (Nakagawa-Goto and Crimmins 2011a) and top fragment of bryostatin 11 have also been described (Nagakawa-Goto and Crimmins 2011b). The synthesis of bryostatin analouges (bryologs) has also been reported (Wender and Reuber 2011;Wach and Gademann 2012). These are simpler and therefore lend themselves more easily to synthesis .…”
Section: Bryostatins and Other Substances From Bryozoansmentioning
confidence: 85%